2020
DOI: 10.2174/1871520620666200615133011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Therapeutic Targets for Anticancer Drugs in Lung Cancer Therapy

Abstract: : MicroRNAs (miRNAs) are short, non-coding RNA molecules that regulate gene expression by translational repression or deregulating of messenger RNAs. Accumulating evidence suggests miRNAs play various roles in the development and progression of lung cancers. Although their precise roles in targeted cancer therapy are currently unclear, miRNAs have been shown to affect the sensitivity of tumors to anticancer drugs. A large number of recent studies have demonstrated that some anticancer drugs exerted antitumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 155 publications
0
4
0
Order By: Relevance
“…Although their definite role in targeted treatment is not yet clear, miRNAs can alter tumor sensitivity to antitumor drugs ( Liu et al, 2020 ). A number of studies have shown that some antitumor drugs exert their antitumor effect via affecting miRNAs and their targeted genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although their definite role in targeted treatment is not yet clear, miRNAs can alter tumor sensitivity to antitumor drugs ( Liu et al, 2020 ). A number of studies have shown that some antitumor drugs exert their antitumor effect via affecting miRNAs and their targeted genes.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in TGFBR2 expression levels are reported in CRC 22,25 . Small non‐coding RNAs, such as microRNAs (miRNAs) are well known as the post‐transcriptional gene expression regulators in various kinds of cancers, such as CRC 26–30 . For example, miR‐4,319, miR‐143, miR‐20a and miR‐145 are associated with CRC progression 31–34 .…”
Section: Introductionmentioning
confidence: 99%
“…22,25 Small non-coding RNAs, such as microRNAs (miRNAs) are well known as the posttranscriptional gene expression regulators in various kinds of cancers, such as CRC. [26][27][28][29][30] For example, miR-4,319, miR-143, miR-20a and miR-145 are associated with CRC progression. [31][32][33][34] It has been reported that the miR-20a-5p may affect the cellular phosphoinositide 3-kinase-Akt, mitogen-activated protein kinase and TGF-β signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…They have been certified as essential epigenetic factors that regulate gene expression via interacting with the 3’-untranslated region of their downstream target genes, ultimately triggering translation suppression or mRNA degradation 16 . Aberrant miRNA expression is widely observed in NSCLC occurrence and development and contributes to an extensive range of malignant behaviors 17 . Recently, an increasing number of studies have highlighted that the competing endogenous RNA (ceRNA) regulatory network has a role in NSCLC 18–20 .…”
Section: Introductionmentioning
confidence: 99%